Pelatihan Pembuatan Nugget Tempe bagi Majelis Taklim Al-Hidayah Kelurahan Limbungan - David Setiawan; Hazra Yuvendius; Elvira Zondra (Asosiasi Dosen Akuntansi Indonesia, 2021)
Tempe is a food that is familiar and commonly found in our country, so that the raw material for tempeh is easily found in markets and stalls around our homes. In the presentation, sometimes fried tempeh, some even innovate so that the appearance of tempeh is attractive and the feeling of wanting to enjoy it from its shape and packaging. One of the innovations to make tempeh dishes interesting to enjoy is the tempeh nuggets. Tempeh nuggets are almost the same as meat nuggets, but the raw material used to replace meat is tempeh so that tempeh nuggets are cheaper, nutritious and taste no less satisfying than meat nuggets. In this service, the team provided training for majelis taklim women to make tempe nuggets, from the training carried out, the enthusiasm of the participants was quite high, it was evident that there were many questions and the desire to do it themselves in the process of making the tempe nuggets..